Self-preservation positions in family communications: parent – child interaction - Sekera, Ondřej (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This paper describes the part of results of research into family communications. Our two years’ investigation was targeted at communication between parents and children. The focus was on so called “Satir Models” of self-preservation positions taken by parents in family communications most frequently. The data come from authentic recordings of common communications in families related to specific situations (for example, children getting ready for a day at school, during art and craft activities, sitting at the table, etc.). Our aim is to describe and analyse concrete examples of family communications used by parents in the child directed speech to fulfil the self-preservation strategies.
Keywords: self-preservation position; parent – child interaction; communication functions in language; congruence; incongruence